MEASUREMENT OF A BALANCED SCORECARD AND SWOT ANALYSIS IN CONSUMER LENDING STRATEGY OF BANK SUMSEL BABEL MUNTOK (Journal of Business Management and Accounting, 2024)
The balanced scorecard measures the overall performance of the organization from four perspectives: financial, customer, internal business process, learning, and growth. Under a quantitative research design, this research tries to measure the performance of consumer lending distribution at Bank Sumsel Babel Muntok branch by using Balance Scorecard perspectives, followed by a SWOT analysis and an assessment of the company's position according to the Internal External Matrix. The object of this research is one of the regional development bank's branches. Primary data were collected through a questionnaire, and secondary data were obtained through the financial report PT Bank Pembangunan Daerah Sumatera Selatan dan Bangka Belitung (Bank Sumsel Babel). The matrix aligns with the company's SWOT, and the results are then explained using the IFAS Matrix (Strength - Weakness) and EFAS Matrix (Opportunities - Threats). The results of the IFAS and EFAS Matrix are depicted in the Cartesian SWOT Diagram. Based on the Cartesian SWOT Diagram, the distribution of multipurpose lending Bank Sumsel Babel Muntok is in quadrant I, where the strategy that needs to be implemented is aggressive. An aggressive strategy makes the organization's strengths in maximizing the opportunities available.